Quantification of load-dependent changes in the collagen fiber architecture for strut chordae tendineae-leaflet insertion of porcine atrioventricular heart valves - Ross, Colton J. (Biomech Model Mechanobiol, 2020)
Atrioventricular heart valves (AHVs) regulate the unidirectional flow of blood through the heart by opening and closing of the leaflets, which are supported in their functions by the chordae tendineae (CT). The leaflets and CT are primarily composed of collagen fibers that act as the load-bearing component of the tissue microstructures. At the CT-leaflet insertion, the collagen fiber architecture is complex, and has been of increasing focus in the previous literature. However, these previous studies have not been able to quantify the load-dependent changes in the tissue’s collagen fiber orientations and alignments. In the present study, we address this gap in knowledge by quantifying the changes in the collagen fiber architecture of the mitral and tricuspid valve’s strut CT-leaflet insertions in response to the applied loading by using a unique approach, which combines polarized spatial frequency domain imaging with uniaxial mechanical testing. Additionally, we characterized these microstructural changes across the same specimen without the need for tissue fixatives. We observed increases in the collagen fiber alignments in the CT-leaflet insertion with increased loading, as described through the degree of optical anisotropy. Furthermore, we used a leaflet-CT-papillary muscle entity method during uniaxial testing to quantify the chordae tendineae mechanics, including the derivation of the Ogden-type constitutive modeling parameters. Results from this study provide a valuable insight into the load-dependent behaviors of the strut CT-leaflet insertion, offering a research venue to better understand the relationship between tissue mechanics and the microstructure, which will contribute to a deeper understanding of AHV biomechanics.